2008
DOI: 10.1111/j.1475-1313.2008.00539.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in corneal sensitivity and tear physiology after phacoemulsification

Abstract: Deterioration in corneal sensitivity and tear physiology is seen immediately after phacoemulsification. Corneal sensitivity does not return to preoperative levels until 3 months postoperatively whereas the tear functions recover within 1 month.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
115
1
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(146 citation statements)
references
References 48 publications
(43 reference statements)
7
115
1
9
Order By: Relevance
“…The change in the corneal sensitivities at the other areas of the cornea was not found statistically significant. It has been reported that the corneal sensitivity had returned to preoperative levels after 3 months, in a previous study with 4.1 mm corneal incision phacoemulsification [2]. In our study, the mean corneal sensitivity of superior incision site decreased statistically significant at 3 days after microincisional cataract surgery with 2.2 mm clear corneal incision.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…The change in the corneal sensitivities at the other areas of the cornea was not found statistically significant. It has been reported that the corneal sensitivity had returned to preoperative levels after 3 months, in a previous study with 4.1 mm corneal incision phacoemulsification [2]. In our study, the mean corneal sensitivity of superior incision site decreased statistically significant at 3 days after microincisional cataract surgery with 2.2 mm clear corneal incision.…”
Section: Discussionsupporting
confidence: 63%
“…Therefore, temporary dry eye symptoms might develop until the nerves regenerate again [2,10]. Most surgical procedures, especially surgical incisions that cause denervation of the cornea, also result in impaired epithelial wound healing, increased epithelial permeability, decreased epithelial metabolic activity and loss of cytoskeletal structures associated with cellular adhesion [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 A corneal incision, notwithstanding its small size, can cause certain corneal irregularities, favouring tear film ruptures. Moreover, an alteration in central corneal sensitivity has been found in patients who have undergone cataract surgery, 30 secondary to the corneal nerve section, which may potentially disrupt the neural loop, reducing tear secretion by the lacrimal gland. 31 The increase in TBUT and the improvement of the OSDI and its subscales after treatment with HP-Guar may be due to its peculiar mechanism of action.…”
Section: Discussionmentioning
confidence: 99%